The Influence Of Digital Transformation And Transparency On Ziswaf Payment Decisions And Its Impact On Millennial Loyalty - Ahmad Zaenal Mustafa; Budiman Abdulah (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study investigates the influence of digital transformation and transparency on ZISWAF (Zakat, Infaq, Sadaqah, and Waqf) payment decisions and their subsequent impact on millennial loyalty, with a focus on LAZISMU DKI Jakarta. Employing a quantitative, associative research approach, data were collected from 150 millennial respondents through structured questionnaires. Structural Equation Modeling using Partial Least Squares (SEM-PLS) was applied for data analysis. The results demonstrate that digital transformation significantly affects both payment decisions and user loyalty, while transparency does not directly influence payment decisions but contributes to loyalty. Furthermore, ZISWAF payment decisions are shown to have a positive and significant effect on millennial loyalty. These findings underscore the strategic importance of service digitization and transparent fund management in enhancing youth engagement and long-term donor commitment in Islamic philanthropic institutions. Keywords: Digital Transformation, Transparency, ZISWAF, Payment Decision, Millennial Loyalty